2017
DOI: 10.1002/jqs.2998
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of MIS 3 glaciation using cosmogenic radionuclide and single grain luminescence ages, Kanas Valley, Chinese Altai

Abstract: Previous investigations observed a period of major glacial advances in Central Asia during marine oxygen isotope stage (MIS) 3 (57–29 ka), out of phase with global ice volume records. We have re‐examined the Kanas moraine complex in the Altai Mountains of Central Asia, where an MIS 3 glaciation had been previously inferred. New and consistent cosmogenic exposure and single‐grain luminescence ages indicate that the Kanas complex was formed during MIS 2 (29–12 ka), which brings its timing in line with the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…While we observe incipient platy structures in sediments dated to terminal MIS 3 and early MIS 2 (e.g., layer 9, deposited between about 40 and 20 ka), and thus overlapping with the coldest period of the last glacial cycle, the platiness is best expressed in layers that accumulated during the preceding, comparatively warm MIS 3. There is debate surrounding the synchronicity of glacial expansion in the Altai with global climate proxies 64,65 , potentially associated with increased moisture availability in central Asia during MIS 3 relative to MIS 2, which was drier. The Denisova Cave microstratigraphic record may, therefore, document both cold and relatively humid conditions 66 , sufficient to develop platy microstructures in the near-surface, cave floor sediments.…”
Section: Discussionmentioning
confidence: 99%
“…While we observe incipient platy structures in sediments dated to terminal MIS 3 and early MIS 2 (e.g., layer 9, deposited between about 40 and 20 ka), and thus overlapping with the coldest period of the last glacial cycle, the platiness is best expressed in layers that accumulated during the preceding, comparatively warm MIS 3. There is debate surrounding the synchronicity of glacial expansion in the Altai with global climate proxies 64,65 , potentially associated with increased moisture availability in central Asia during MIS 3 relative to MIS 2, which was drier. The Denisova Cave microstratigraphic record may, therefore, document both cold and relatively humid conditions 66 , sufficient to develop platy microstructures in the near-surface, cave floor sediments.…”
Section: Discussionmentioning
confidence: 99%
“…The proglacial lacustrine sediments at Khurgan Nuur (Figure 2, A2), which probably had been eroded and incorporated into an advancing glacier, indicate a glacial stage before and after 88-85 ka. In combination with the moraine ages reported by Poetsch (2017;81-78 ka) from the Turgen-Kharkhiraa Mountains and by Gribenski et al (2018;79-63 ka) at Kanas Lake, these glacial advances can be classified into the period MIS 5a-b. Devyatkin (1981) assumed a high paleolake level at Khyargas Nuur (20) between 90 and 76 ka.…”
Section: Evaluation Of Late Pleistocene Periods Of Environmental Changementioning
confidence: 71%
“…In addition, Reuther et al (2006) reported cataclysmic outburst floods from a big lake, which existed in the Chuja basin due to glacial damming, around 18 ka (Gribenski et al, 2018). Gribenski et al (2018) examined glacial deposits around the Kanas Lake (6), which is situated in the southwestern part of the Altai within Chinese territory. The authors reported MIS 2 for the lLGM and another glacial advance around late MIS 5/MIS 4, but they could not confirm the assumed MIS 3 advance by Zhao et al (2013) and Xu et al (2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations